Model Dialog Islam-Kristen Di Kampung Serta Sumbangsihnya Bagi Teologi Kerukunan Agama-Agama - Rintjap, Aurelia Nafra Sheren; Mawuntu, Marhaeni Luciana (UPT Penelitian Fakultas Teologi Universitas Kristen Indonesia Tomohon, 2024)
The socio-cultural, religious, and political plurality in the life of the people of Tomohon city is a blessing that must be thanked and an opportunity to strengthen the bond of harmony. The Islamic-Christian communities in Java, Tomohon and Tumatangtang I villages are a clear proof that people can coexist. This article is prepared using qualitative research in order to review what the conditions are in the research site, as well as take the data needed to conduct analysis. To be able to get to know and understand each other between these two religious communities, a forum is needed, namely a communication forum that can send religious adherents to build a dialogue. The pattern of dialogue created in community life aims to build a relationship and help religious believers to be more familiar.